Fair wages and effort provision: Combining evidence from the lab and the field - Alain Cohn; Ernst Fehr; Lorenz Goette (University of Zurich, Department of Economics, 2013)
The presence of workers who reciprocate higher wages with greater effort can have important consequences for labor markets. Knowledge about the determinants of reciprocal effort choices is, however, incomplete. We investigate the role of fairness perceptions and social preferences in workers' performance in a field experiment in which workers were hired for a one-time job. We show that workers who perceive being underpaid at the base wage increase their performance if the hourly wage increases, while those who feel adequately paid or overpaid at the base wage do not change their performance. Moreover, we find that only workers who display positive reciprocity in a lab experiment show reciprocal performance responses in the field, while workers who lack positive reciprocity in the lab do not respond to the wage increase even if they feel underpaid at the base wage. Our findings suggest that fairness perceptions and social preferences are key in workers' performance response to a wage increase. They are the first direct evidence of the fair-wage effort hypothesis in the field and also help interpret previous contradictory findings in the literature.
Keywords: C93; J31; M52; 330; Fairness Perception; Positive Reciprocity; Field Experiment; Wage Increase; Lohn; Gerechtigkeit; Wahrnehmung; Austauschtheorie (Soziologie); Test